Experimental Analysis of Anchor Bolt in Concrete under the Pull-Out Loading. (2017) - Hariyadi; Munemoto, Satoru; Sonoda, Yoshimi
Abstract: The design of pull-out strength of anchor bolt in concrete is generally based on standards which are assumed to have a single crack failure and the uniform stress. However, in real phenomenon these assumptions are not reliable and a combination of failure modes between the cone and bond failure is commonly found. This research was conducted to analyze the failure mechanism and the strength of the anchor bolt under static pull-out load. Normal strength of concrete-mortar block and the shallow depth of anchor bolt was used in this research. The failure mode, reaction force, and concrete cone stress will be discussed and compared to the design standards. The experimental results clearly show that a combination failure mode between the cone and bond failure of anchor bolt was found, consequently the depth of the cone failure part reduced and the angle of cone slope narrowed. The cone stress and loading capacity of the experimental result is extremely lower than the design standards, which is around a half. Therefore a certain safety factor is required to guarantee the safety of anchor bolt structures.